2018
DOI: 10.1136/bmjopen-2017-020464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peritonitis and mortality in patients treated with continuous ambulatory peritoneal dialysis (CAPD) in Africa: a protocol for a systematic review and meta-analysis

Abstract: IntroductionContinuous ambulatory peritoneal dialysis (CAPD) is the ideal modality for renal replacement therapy in most African settings given that it is relatively cheaper than haemodialysis (HD) and does not require in-centre care. CAPD is, however, not readily utilised as it is often complicated by peritonitis leading to high rates of technique failure. The objective of this study is to assess the prevalence of CAPD-related peritonitis and all-cause mortality in patients treated with CAPD in Africa.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The results revealed that PD catheterrelated infections were the most frequent complication (38.8%). This result was compatible with those at other large medical centers in the literature (17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed that PD catheterrelated infections were the most frequent complication (38.8%). This result was compatible with those at other large medical centers in the literature (17)(18)(19).…”
Section: Discussionsupporting
confidence: 92%
“…The study protocol was registered in the International Prospective Register of systematic reviews and has been published. 12 We searched PubMed, Embase, Web of Science and Africa Journal Online for relevant studies on peritonitis related to the treatment of patients with ESKD treated with PD. The searches were limited to studies performed in Africa and published from 1 January 1980 to 31 December 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Peritonitis is a major complication in PD patients and is associated with an increased risk of technique failure and in some cases death. [30][31][32] The 2016 ISPD (International Society for Peritoneal Dialysis) peritonitis recommendations stated that centres should aim to have a rate of ≤ 0.5 episodes/patient-year. 33 Additionally, the risk of peritonitis is increased when wet contamination episodes occur without antibiotic prophylaxis.…”
Section: Open Accessmentioning
confidence: 99%